Mikroflora Jamur Produk Kakao Kering Serta Kemungkinan Penghambatan Jamur Penghasil Toksin oleh Bakteri Asam Laktat dan Bacillus Spp. - Anton Rahmadi (Balai Riset dan Standardisasi Industri Samarinda, 2016)
Mycotoxins contamination in sun dried cocoa has become a concern in public health but it has not been studied thoroughly yet. This research aimed to understand the ecology of fungal contamination in relation to the occurrence of toxigenic metabolites in Indonesian and Australian fermented cocoa. The beans were surface disinfected with 0.4% chlorine prior to deposite onto Dichloran 18 % Glycerol Agar (DG-18. OXOID). Total fungal count was obtained from serial dilutions on DG-18 medium. Streaking onto Dichioten Rose Bengal Chloramphenicol Agar (DRBC, OXOID) purified a specific mould colony. Simultaneously. Aspergillus sec. Flavi colonies were confirmed using Aspergillus Flavus Parasiticus Agar (AFPA. OXOID). The confirmatory test was mainly based on morphological examinalion under phase contrastmicroscope. Fungal population in Indonesian beans varied belween 10’4 – 105cfu/g, while the populations on Queensland beans were consistently low (<100- 2.5 x 102 cfu/g). However. there was a high incidence of potentiallymycotoxiqenic filamentous fungi on all bean samples. The main species wereAspergillus flavus, Aspergillus niger. Aspergillus wentii. Aspergillus clavatus. Penicillium citrinum, and Penicillium spinolosum. The beans from Queensland gave high counts of Bacillus species and lactic acid bacteria and it is suggested that they served as natural biocontrol againts against the filamentous fungi.